DYNAMIC RETEAMING the art and wisdom of changing teams;the art and wisdom of changing teams - HELFAND, HEIDI (O'REILLY MEDIA, INCORPORA, 2020)
Your team will change whether you like it or not. People will come and go. Your company might double in size or even be acquired. In this practical book, author Heidi Helfand shares techniques for reteaming effectively. Engineering leaders will learn how to catalyze team change to reduce the risk of attrition, learning and career stagnation, and the development of knowledge silos. Based on research into well-known software companies, the patterns in this book help CTOs and team managers effectively integrate new hires into an existing team, manage a team that has lost members, or deal with unexpected change. You'll learn how to isolate teams for focused innovation, rotate team members for knowledge sharing, break through organizational apathy, and more.